Comparison of Deposition Methods of ZnO Thin Film on Flexible Substrate - A. A.M. Idris; R. Arsat; M. K. Ahmad; F. Sidek (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper reports the effect of the different deposition methods towards the ZnO nanostructure crystal quality and film thickness on the polyimide substrate. The ZnO film has been deposited by using the spray pyrolysis technique, sol-gel and RF Sputtering. Different methods give a different nanostructure of the ZnO thin film. Sol gel methods, results of nanoflowers ZnO thin film with the thickness of thin film is 600nm. It also produces the best of the piezoelectric effect in term of electrical performance, which is 5.0 V and 12 MHz of frequency which is higher than other frequency obtained by spray pyrolysis and RF sputtering.